Asking the Oracle - Crawford, Kate (Astro Noise, ed. Laura Poitras, 2016)
For many reasons, this database is a machine for producing anxiety. The interface is query driven: it centers on a search box. Like a highly classified version of Google or Reddit’s Ask Me Anything, the only way to make discoveries is to throw some terms out there. There is no easy browsing or pretty visualization of the repository itself. Instead, you must begin by phrasing any questions you have about the military-intelligence complex in the form of Boolean search terms. So I type in words. It feels exhilarating, terrifying: Where to begin? How about something about cryptographic techniques, specific algorithms, or existing NSA programs? Thousands of search results. Days of work just to figure out what will be relevant. Instead, I try increasingly idiosyncratic, unusual combinations. Even then, the result is often dozens of documents, each with its own suggestive paths to follow. This is just the first challenge of the archive.